Systematic Review: Efek Nanoplastik terhadap Metilasi DNA pada Manusia - Anggit Wirama Siwidati; Abdul Rohim Tualeka (Media Gizi Kesmas, 2023)
Background: Along with the times, plastic pollution is increasing and this is a problem throughout the world, especially in developing countries due to its very large amount, persistent nature and widespread use. Objectives: The purpose of this systematic review is to determine the effect of nanoplastics on deoxyribonucleic acid (DNA) methylation in humans Methods: The method used is PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses). Data search in the form of articles or journals is carried out using the keywords "nanoplastics" and "DNA methylation". The inclusion criteria used were human population, nanoplastic effect, type of nanoplastic, amount and time of exposure, and DNA methylation. The data source used comes from Google Scholar, with the publication year starting from 2017-2022, and the language used is English Discussion: total data based on searches using the keywords "nanoplastics" and "DNA Methylation" (n=94), focusing on the study and research articles and free full text with the year of publication being the last 5 years (n=29), then adjusting the inclusion criteria (n=13). Conclusions: According to the results of the systematic review, it was concluded that there is a relationship between nanoplastics and DNA methylation. However, these results have limitations so it is necessary to conduct research with subjects that focus on workers. In addition, this systematic review has not been able to explain the special effects on workers in the industrial field due to limited literature obtained.